2012
DOI: 10.1002/ange.201201643
|View full text |Cite
|
Sign up to set email alerts
|

An NHeterocyclic Carbene/Lewis Acid Strategy for the Stereoselective Synthesis of Spirooxindole Lactones

Abstract: A cooperative catalysis approach for the enantioselective formal [3+2] addition of α,β-unsaturated aldehydes to isatins has been developed. The N-heterocyclic carbene (NHC)-catalyzed homoenolate annulations of β-aryl enals require the addition of lithium chloride for high levels of enantioselectivity. This NHC-catalyzed annulation provides efficient access to the 3-hydroxy indole skeleton and has been applied to the first eantioselective total synthesis of maremycin B. Keywordscatalysis; asymmetric synthesis; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(28 citation statements)
references
References 69 publications
0
26
0
2
Order By: Relevance
“…[14] Zuvor hatte unsere Gruppe über eine NHC-katalysierte intramolekulare Michael-Reaktion berichtet, die mit hoher Enantioselektivitätz uR ingsystemen führt (Schema 5b). [18] Bei Kontrollreaktionen zeigte sich, dass der Austausch von Lithium gegen verschiedene Lewis-Säuren (Na + oder K + )o der die Sequestrierung mit Kronenether zu einer geringeren Enantioselektivitätführte. [16] Stark chelatisierende Substrate waren ein vorrangiges Ziel fürd ie kooperative NHC/Lewis-Säure-Katalyse.…”
Section: Introductionunclassified
“…[14] Zuvor hatte unsere Gruppe über eine NHC-katalysierte intramolekulare Michael-Reaktion berichtet, die mit hoher Enantioselektivitätz uR ingsystemen führt (Schema 5b). [18] Bei Kontrollreaktionen zeigte sich, dass der Austausch von Lithium gegen verschiedene Lewis-Säuren (Na + oder K + )o der die Sequestrierung mit Kronenether zu einer geringeren Enantioselektivitätführte. [16] Stark chelatisierende Substrate waren ein vorrangiges Ziel fürd ie kooperative NHC/Lewis-Säure-Katalyse.…”
Section: Introductionunclassified
“…Notably, the use of NHC/Lewis acid or Brønsted acid cooperative catalysis for enhancing selectivity and incorporating previously inactive reaction partners has seen significant success. [7],[8] Despite the demonstrated utility of chiral Brønsted acids (CBAs) for a variety of asymmetric transformations, [9],[10],[11] the combination of NHCs and chiral Brønsted acids represents new opportunity for small molecule activation. Herein we report a general cooperative NHC/chiral Brønsted acid strategy to achieve a highly enantioselective addition of alkynals to α-ketoesters (Figure 1).…”
mentioning
confidence: 99%
“…of lithium chloride (entry 3). [7f] Even though the reaction yield was poor, this result indicated that lithium cations may be activating methyl benzoylformate toward addition. The introduction of chiral Brønsted acid F ( 20 mol %) with achiral NHC from B produced a significant increase in yield (54%), but the annulation product was effectively racemic (entry 4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Encouraged by this result, an extensive screening of the reaction parameters, such as solvent, base, and temperature, was conducted, but the conversion could not be increased above 20 %. [11] When the benzhydrylpyrrolidine moiety was replaced with the common benzylpyrrolidine system, a significant reduction of ee (91 to 82 %) was observed. A crystal structure of 5 b is shown in Figure 1.…”
mentioning
confidence: 99%